THU0730-HPR THE MAP OF THE RHEUMATOLOGY NURSE CLINICAL AND RESEARCH INTERVENTIONS IN THE VALENCIAN REGION (SPAIN). (June 2019) - Herranz, Carmen Nájera; Olmos, Inés Cánovas; García, Elena Grau; Jordá, Amelia Carbonell; Torre-Aboki, Jenny de la; Rodríguez, Oscar Aranega; Trull, Isabel Balaguer; Cano, Catalina; Amorós, Carmen Maria Francés; Gallego, Lola Gil; Clan, Alicia Gómez; Martín, Elizabeth Marín; et al.
Abstract : Background: There is none defined competences framework for Rheumatology Nursing at the moment in Spain. This fact leads to an heterogeneous roles and interventions in each Rheumatology department which has not ever been described nor quantified. Objectives: To describe and quantify the rheumatology Nursing interventions in the Valencian Region (Spain). Methods: A descriptive study was performed by the completion of an online questionnaire with a list of clinical and research intervention. The questionnaire was sent to the Head of Rheumatology Department of 33 public hospitals from the Valencian Region. Results: 32 hospitals of the Valencian Region fulfilled the questionnaire: 15 from Valencia, 13 from Alicante and 4 from Castellón. 50% of the hospitals had a Rheumatology nurse. In those hospitals, 50% had only 1 Rheumatology nurse working at the moment. The maximum Rheumatology nurses working in the same hospitals were 4; 2 hospitals used to have a Rheumatology nurse but do not have it anymore at this moment. 11 hospitals have an auxiliary nurse (3 of them without nurses and 8 with nurses). The year of incorporation of the Rheumatology nurse in the Department was quite heterogeneous, being the earlier in 1992 and the last incorporation in 2017. The nurses worked mainly in a Rheumatology department full time (68.75%). The 81% of the hospitals had an specific nursing agenda but only 7 hospitals had a monographic nurse-led clinic (osteoporosis nurse-led clinic -25%-, intravenous treatments nurse-led clinic -12.5%- or cardiovascular risk nurse-led clinic -6.25%) Nurses clinical interventions are very heterogeneous covering the patient clinical management and practice nurses intervention activities. Nurses organized patient education workshops in 25% hospitals. In 11 hospitals, nurse undertook teaching activities. 56% participating in scientific workshops/congress, 44% teaching undergraduated nurses/registered nurses and 37.5% teaching other healthcare professionals. In 11 hospitals, nurses undertook research activities. In 2 hospitals an specific research nurse was available. 56% of nurses participated in clinical trials, 50% participated in research projects and 50% participated in scientific congress. 25% of nurses lead research projects. In 12 hospitals, nurses belong to a scientific society; in 11 hospitals, nurses participated in regional, national and/or international nurses working groups. Conclusion: In at least 50% of the hospitals from the Valencian Region, nurse activity was registered. There are heterogeneous clinical activities performed by nurses. This fact raised the issue of the importance of having unified criteria for nurse's intervention and competences framework comparable in each and every hospital. Teaching and research were also a common interventions mentioned. These activities are necessary for a constant recycling and updating of the nurses and will help to gain the necessary visibility for the rheumatology nurses. Disclosure of Interests: None declared